A model-based design for coating materials including perlite-peanut shell-volcanic lava stone ternary system - Celik, Bilge; Acarali, Nil (TAYLOR & FRANCIS LTD, 2022)
Cellulose in the fibrous structure as the main structural component in the cell wall of plants was formed by the combination of three thousand or more glucose molecules. It was a natural polymer synthesized by a large number of living microorganisms. In this study, it was aimed to observe the performance of peanut shells physically added to the water-based coating to increase the viscosity of the coatings. In addition, volcanic lava stone and perlite stone were added to the coating to improve its properties, such as adhesion, hydrophobicity, corrosion resistance, and hiding power. The effect of cellulose-based material on the viscosity of the coating was determined using the Design Expert Optimization Method. In the experimental design method, the experimental set was created as peanut shell, volcanic lava stone, perlite stone, and additives were added as 0-6% by weight of the coating. By using the method, the most suitable process parameters were specified and the effects of the additives added to the coating were examined, comparatively. As a result, it was found that cellulose-derived organic additives and other additives improved the various properties of the coating. It was seen that the perlite-peanut shell-volcanic lava stone ternary system could be evaluated for industrial coatings.
Keywords: Peanut shell; coating; viscosity; volcanic lava stone; cellulose; OPTIMIZATION; BORNE; Engineering; Materials Science; Mechanics